Between Form and Content: Narrative Typology, Metafiction and Ideology in The Thousand and One Nights. - Dolcerocca, Özen Nergis (Fabula, 2021)
With few exceptions, narrative theory does not ordinarily consider the self-reflexive capacity of The Thousand and One Nights beyond its canonical instance of framing, and Arabic literary scholarship does not ordinarily engage with its narratological aspects. This article proposes a narratological approach for a systematic breakdown of story cycles through abstraction, partly by making use of computer programming language, in order to demonstrate the narrative typology in the Nights. It argues that repetitions, transpositions, substitutions, and reversals testify to tensions between the overt ideology of the text and the counter discourse that unsettles this logic, concealed in its poetics. The article thereby aims to bring some of the core concepts of narrative theory into dialogue with the Nights scholarship, and to contribute to a theoretical conversation about ideological critique in narrative analysis, particularly within the pre-modern storytelling tradition.